2015
DOI: 10.1002/jsfa.7383
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of a sustained-release buckwheat noodle

Abstract: These findings indicate that the controlled use of hydrophilic colloids and starches in manufacturing noodles could modulate the glucose sustained-release. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Dietary fiber also can create a protective barrier on the surface of starch granules by encapsulating and cross-linking them (Liu et al, 2018). This phenomenon can retard the contact between starch granules and amylase and reduce the amount of glucose released (Wang et al, 2016). Ge et al (2021) also observed a similar phenomenon where the addition of pumpkin powder to bread resulted in a more consistent and stable gel network structure, attributed to its high dietary fiber content.…”
Section: Glucose Release Amount During Simulated Digestion In Vitromentioning
confidence: 98%
See 4 more Smart Citations
“…Dietary fiber also can create a protective barrier on the surface of starch granules by encapsulating and cross-linking them (Liu et al, 2018). This phenomenon can retard the contact between starch granules and amylase and reduce the amount of glucose released (Wang et al, 2016). Ge et al (2021) also observed a similar phenomenon where the addition of pumpkin powder to bread resulted in a more consistent and stable gel network structure, attributed to its high dietary fiber content.…”
Section: Glucose Release Amount During Simulated Digestion In Vitromentioning
confidence: 98%
“…The rheology of the simulated gastric and gastrointestinal digesta of TAB 0 , TAB 1 , TAB 3 , TAB 5 , and TAB 10 was measured using an advanced rotational rheometer (TA: Discovery HR-20) (Wu et al, 2016). The aluminum plate diameter is 40 mm.…”
Section: Rheological Measurements Of Bread Digestamentioning
confidence: 99%
See 3 more Smart Citations